Differences in physical fitness and throwing velocity among elite and amateur female handball players - Granados, C.; Izquierdo, M.; Ibanez, J.; Bonnabau, H.; Gorostiaga, E. M. (International Journal of Sports Medicine, 2007)
This study compared physical characteristics (body height [BH], body mass [BM], body fat [BF], and fat free mass [FFM]), one repetition maximum bench press (1RMBP), jumping explosive power (VJ), handball throwing velocity, power-load relationship of the leg and arm extensor muscles, 5- and 15-m sprint running time, and running endurance in elite (n = 16; EF) and amateur (n = 15; AF) female handball players aged 17 - 38. Results revealed that, compared to AF, EF players presented similar values in body mass and percent body fat, but higher values (p < 0.001 - 0.05) in BH (6 %), FFM (10 %), 1RMBP (23 %), VJ (10 %), handball throwing velocity (11 %), power-load relationship of the arm (25 %) and leg (12 %) extensors, as well as 5- and 15-m sprint (3 - 4 %) and endurance running velocities (13 %). Univariate regression analyses showed that 1RMBP was associated with throwing velocity (R2 = 0.64). The higher absolute values of maximal strength and muscle power, although explained by the differences in fat free mass, will give EF an advantage to sustain certain handball game actions. The association between 1RMBP and throwing velocity suggests that throwing velocity values in female handball players depend more on maximal strength than on the capacity to move low loads at high velocities, during elbow extension actions.